Hubungan Pengetahuan Dan Sikap Keluarga Terhadap Tingkat Kecemasan Dalam Merawat Anggota Keluarga Dengan Gangguan Jiwa (ODGJ) - Gusdiansyah, Edo; Welly, Welly (REAL in Nursing Journal, 2024)
Background: The problem often experienced by families of people with mental disorders (ODGJ) is increased anxiety in caring for them, such as tension, worry, fear, sleep disturbance, impaired intelligence, and depression. Family knowledge and attitudes towards ODGJ are considered important factors that can affect the level of family anxiety in caring for them. This study aims to examine the relationship between family knowledge and attitude towards the level of anxiety in caring for family members with mental disorders (ODGJ). Methods:This study used a quantitative method with a cross-sectional approach. Data were collected through questionnaires, namely knowledge referring to Maromon's research (2020), attitudes referring to Safitri's research (2022) and anxiety levels using the HARS (Hamilton Anxiety Rating Scale) questionnaire with a sample of 97 families who have members with ODGJ in the andalas puskemas area. Data analysis was performed using the Chi Square test. Results: The results obtained were more than half, namely 56 (57.7%) respondents had a mild level of anxiety, more than half, namely 54 (55.7%) respondents had low knowledge, more than half, namely 58 (58.9%) respondents had a negative attitude in caring for people with mental disorders (ODGJ). There is a relationship between knowledge (p = 0.000), attitude (p = 0.000) with family anxiety level in caring for ODGJ. Conclusion: It is expected that nurses at the health centre can provide health education on how to care for ODGJ at home and can help reduce their anxiety in daily care.